Use of ceramic materials in cylinder piston groups - Kushaliev, Даурен; Korabay, Ризабек (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
This article talks about the use of ceramic materials to increase the efficiency and wear resistance of the internal combustion engine design. The use of ceramic materials is due to their high resistance to temperature factors, as well as a reduced coefficient of friction. More suitable materials to use are silicon carbides and nitrides. The raw materials for their production are substances widespread in nature: quartz sand, feldspar and kaolin. manufacturing parts of the required shape from them by hot pressing or sintering of the base material using binders. The technique of liquid stamping with ceramic inserts refers to the production of composite parts in metallurgical engineering using the methods of casting, cold casting, casting with crystallization under pressure, as well as thixocasting and thixo-stamping. The tool has a prefabricated metal-ceramic insert.